Adult ADHD and sleep disorders: Prevalence, severity and predictors of sleep disorders in a sample of Italian psychiatric outpatients. (April 2022) - Valsecchi, Paolo; Nibbio, Gabriele; Rosa, Jennifer; Vita, Antonio
Highlights: Sleep disorders were more frequent and severe in people with adult ADHD compared to other psychiatric outpatients in our sample of 634 participants. ADHD diagnosis, multiple psychiatric comorbidity and history of suicide attempts emerged as individual predictors of worse sleep disturbances. Sleep disturbances might represent an intrinsic feature of ADHD and should be routinely evaluated and monitored in this population. Abstract: Objective: Sleep disorders are frequent in adult subjects diagnosed with ADHD. The aims of the present study were to assess the prevalence and the severity of sleep disorders in a sample of Italian psychiatric outpatients, to compare the prevalence and severity of sleep disorders in patients with and without diagnosis of adult ADHD, and to evaluate the role of ADHD as an individual predictor of sleep disturbances severity. Method: 634 outpatients accessing psychiatric services were assessed with the Mini-International Neuropsychiatric Interview (MINI) Plus V. 5.0.0 interview and the Adult ADHD self-report Scale Symptoms Checklist (ASRS)-V 1.1 Short Form. Patients positive to the ASRS-V 1.1 were assessed with the Diagnostic Interview for ADHD in Adults (DIVA) 2.0. Sleep disorders and sleep disturbances' severity were assessed with the PROMIS Adult Sleep Disturbance Scale. Results: Sleep disorders were more frequent ( p  < 0.001) and sleep disturbances were more severe ( d  = 1.26, p  < 0.001) in subjects diagnosed with adult ADHD compared to other outpatients. Among the 44 subjects diagnosed with ADHD, 15 (34.1%) reported no or slight sleep disturbances, 9 (20.5%) a mild sleep disorder, 17 (38.6%) a moderate sleep disorder and 3 (6.8%) a severe sleep disorder. ADHD diagnosis, multiple psychiatric comorbidity and history of suicide attempts emerged as individual predictors of worse sleep disturbances. Conclusion: Sleep disorders are more frequent and severe in subjects diagnosed with ADHD compared to other adult outpatients. Sleep disturbances might represent an intrinsic feature in adult ADHD subjects, presenting important clinical repercussions, and should be routinely evaluated and monitored in this population.